Modern Uzbek Cinematography Development Issues (On the example of the Tashkent International Film Festival "Pearl of the Silk Road") - Ikbal Mamasadikovich Melikuziev (Zien Journals, 2022)
This scientific article analyzes the issues of the development of modern Uzbek cinema, studies their achievements and problems, makes the necessary suggestions and comments. In Uzbek art cinema, in the light of the current state of youth creativity, suggestions and comments will be made to eliminate existing problems.
Keywords: Uzbek cinema; cinematography; historical genre; composition